PENCARIAN INFORMASI UTILITARIAN MELALUI ELECTRONIC WORTH OF MOUTH SERTA DAMPAKNYA TERHADAP PEMBELIAN ONLINE DI LAZADA - Dewi Nuraini; Evianah Evianah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study was conducted to determine the effect of utilitarian information search on online purchases through E-WOM. This research is a quantitative study, with a population of respondents who are LAZADA consumers in Surabaya and the sample technique uses purposive sampling. The number of respondents taken was 70 people. The hypothesis in this study was analyzed using the smart PLS method with the results of H1: Utilitarian information search has a significant effect on accepted online purchases. H2: Utilitarian information search has a significant effect on Electronic Word of Mouth (E- WOM) received. H3: electronic word of mouth (E-WOM) has an effect on accepted online purchases.